Light induces changes in activities of Na+/K+-ATPase, H+/K+-ATPase and glutamine synthetase in tissues involved directly or indirectly in light-enhanced calcification in the giant clam, Tridacna squamosa - Ip, Yuen K.; Ching, Biyun; Hiong, Kum C.; Choo, Celine Y. L.; Boo, Mel V.; Wong, Wai P.; Chew, Shit F. (Frontiers in Physiology, 2015)
The objective of this study was to determine the effects of 12 h of exposure to light, as compared with 12 h of exposure to darkness (control), on enzymatic activities of transporters involved in the transport of NH4+ or H+, and activities of enzymes involved in converting NH4+ to glutamate/glutamine in inner mantle, outer mantle and ctenidia of the giant clam, Tridacna squamosa. Exposure to light resulted in a significant increase in the effectiveness of NH4+ in substitution for K+ to activate Na+/K+-ATPase (NKA), manifested as a significant increase in the Na+/NH4+-activated-NKA activity in the inner mantle. However, similar phenomena were not observed in the extensible outer mantle, which contained abundant symbiotic zooxanthellae. Hence, during light-enhanced calcification, H+ released from CaCO3 deposition could react with NH3 to form NH4+ in the extrapallial fluid, and NH4+ could probably be transported into the shell-facing inner mantle epithelium through NKA. Light also induced an increase in the activity of glutamine synthetase, which converts NH4+ and glutamate to glutamine, in the inner mantle. Taken together, these results explained observations reported elsewhere that light induced a significant increase in pH and a significant decrease in ammonia concentration in the extrapallial fluid, as well as a significant increase in the glutamine concentration in the inner mantle, of T. squamosa. Exposure of T. squamosa to light also led to a significant decrease in the N-ethylmaleimide (NEM)-sensitive-V-H+-ATPase (VATPase) in the inner mantle, and significant increases in the Na+/K+-activated-NKA, H+/NH4+-activated-H+/K+-ATPase and NEM-sensitive-VATPase activities in ctenidia, indicating that light-enhanced calcification might perturb Na+ homeostasis and acid/base balance in the hemolymph, and might involve the active uptake of NH4+ from the environment. This is the first report on light having direct enhancing effects on activities of certain transporters/enz